PELAKSANAAN ANGGARAN COVID-19: UPAYA PELAYANAN PUBLIK DAN PEMBERANTASAN KORUPSI PADA MASA PANDEMI - Jamila Lestyowati (Puslatbang KHAN, 2022)
This study aims to analyze policies and implementation of budget reallocation, refocusing activities, and procurement of goods and services during the Covid-19 pandemic. This activity is a policy step for the Ministry of Finance to provide the budget needed to handle Covid-19 in various fields, namely health, economy, finance, and social affairs. Handling the impact of covid-19 is part of public service to the community. Reallocation and refocusing activities carried out with integrity and prioritizing the public interest will result in activities and budgets that are responsive to handling the impact of a pandemic. This research is exploratory qualitative research using primary data in the form of observations during reallocation, refocusing, and procurement of goods and services and secondary data in the form of regulations, news, literature review. The results showed that through budget reallocation and refocusing activities, the budget collection could be carried out to overcome the impact of covid-19. Supervision of budget execution is needed in the context of handling covid-19 and an attitude of integrity from work unit financial managers.